“Non-significant” Historical Figures and the Corrective Function of Biography - Bartha, Ákos (Dějiny – teorie – kritika, 2025)
In this study, I aim to present some of the methodological experiences I gained by researching the life of Kálmán Zsabka (1897–1971), Iván Szüts (1900–1973), and Kálmán Rátz (1888–1951). To start, I consider that the corrective function of biography can apply equally to the history concerning “famous historical figures” and to the stories of unknown or less-known historical agents who are stuck outside the canon. By exploring “non-significant” historical figures and exceptional normal cases, we can increase our knowledge not only of the individuals we study, but also of their environment. Thus, by fitting small (biographical) stories into the big picture, we can make a small difference in the latter.